2020
DOI: 10.20902/ijctr.2019.130309
|View full text |Cite
|
Sign up to set email alerts
|

Current Drug Repurposing Strategies in Treatment of COVID-19

Abstract: Drug repurposing is the process of finding the new uses of existing drugs. It is one of the emerging methods involved in selecting a molecule for diseases which are communicable and can spread in the general population at a faster pace. The method is selected over conventional drug discovery methods because it is a faster way to bring an existing molecule for a different disease. Ever since COVID-19 pandemic has emerged worldwide use of repurposed drugs has become an important toll to tackle this viral disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…It is observed that adults having greatest immunity to fight against this infection but the disadvantage is they rapidly spread the infection. In 99% of patients shows fever with seriously high temperature, while remaining patients will [12,13].…”
Section: Symptomsmentioning
confidence: 99%
“…It is observed that adults having greatest immunity to fight against this infection but the disadvantage is they rapidly spread the infection. In 99% of patients shows fever with seriously high temperature, while remaining patients will [12,13].…”
Section: Symptomsmentioning
confidence: 99%